STRATEGY OF THE HEAD OF THE COMMUNITY LEARNING ACTIVITY CENTER (PKBM) IN IMPROVING LEARNING AT PKBM AL-MADINAH - Mugni Labib; Yunia Dwi Latifah Yunia (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study uses a qualitative approach with a phenomenological method to explore and deeply understand the experiences and perceptions that arise from the PKBM head's strategy in improving the quality of learning at PKBM Al-Madinah. . This qualitative approach also draws on Sugiyono's framework, which emphasizes naturalistic data collection and thematic analysis to understand.,This approach was chosen because of its ability to naturally describe the state of the object of study, namely the dynamics of the learning process and the role of the PKBM head, with a focus on the meaning created from the experiences of the actors in the field. This method is grounded in the phenomenological theory developed by Edmund Husserl, which emphasizes the importance of uncovering the essence of subjective experience through direct description without prejudice, combined with Martin Heidegger's interpretive approach to understand the existential context of the strategies implemented. Data was collected through in-depth interviews, participatory observation, and document analysis, then processed using phenomenological reduction techniques to identify key themes reflecting the quality of learning at PKBM Al-Madinah. This qualitative approach also draws on Sugiyono's framework, which emphasizes naturalistic data collection and thematic analysis to understand.